Advances in the Combined Use of Adult Cell Therapy and Scaffolds for Brain Tissue Engineering - Garbayo, Elisa; Delcroix, Gaëtan J.-R.; Schiller, Paul C.; Montero-Menei, Claudia N. (IntechOpen, 2011)
None